Bacteria-based self-healing of cement mortars loaded at different levels and exposed to high temperature - Yildirim, Musa; Ozhan, Hacer Bilir; Oz, Hilal Girgin (Emerald Group Publishing Ltd, 2022)
Structures are exposed to various external effects and loads throughout their service life, which can result in failure at a load lower than the design compressive strength. There are cement-based healing systems for repairing such damage, but it is often insufficient. A more effective autonomous healing system is thus needed, and microbial-induced calcite precipitation (MICP) has been studied for this purpose. In this study, bacterial mortar (BM) samples were produced and loaded at different levels of their ultimate compressive stress. The effects of loading were determined and the effectiveness of bacterial treatments was investigated. Experiments were conducted to determine crack healing, compressive strength, water absorption, ultrasonic pulse velocity and high-temperature effects. In the BM samples, the MICP mechanism repaired cracks about 3.5 times larger than the control samples. While the treatment of cracks and damage observed at 90% and 100% loading levels were highly limited thanks to the autogenous system, some properties of the BMs improved as the loading level increased. The MICP mechanism was especially effective in damaged samples under high load levels. In addition, the BMs demonstrated superior physical, mechanical and durability properties at each loading level.
Keywords: bacterial mortar; cracks; durability; self-healing; temperature effects